Design and Simulation of MEMS Sensor for Detection of Arterial Pulse - navghare, Sonali (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
The work presented in this paper describe the design and simulation of a MEMS (Micro Electro Mechanical System) system based piezoelectric sensor for detecting arterial pulse in biomedical application. The study is done through the analysis of square and circular diaphragm made out of piezoelectric and MEMS material. In this work, piezoelectric material is used which work on the principle of piezoelectric effect. In piezoelectric effect, diaphragm reorients under stress, form an internal polarization which result in crystal charge on the crystal face that is proportional to applied pressure. When pressure is applied on diaphragm deformation occurs which converts physical energy into output electrical voltage. For selecting the appropriate geometry and material for sensor design different parameter were checked such as deformation, output voltage, Stress and linearity. FEM analysis is done for circular and square diaphragm on COMSOL Multi-Physics. Comparison of square and circular diaphragm is done on the basis of deformation and Electrical potential. Piezoelectric sensor is designed and simulated with lithium-Niobate and poly-si. Sensitivity obtained for the designed sensor is about 4mV/Kpa.